Sertifikasi Guru Sebagai Upaya Menciptakan Mutu Pendidikan - Tusriyanto Tusriyanto (Tarbawiyah Jurnal Ilmiah Pendidikan, 2014)
The teacher is one of the determining factors for the success of education, therefore, a teacher must be professional, which should be able to master the field of science and teaching to students. The teacher should be a role model in attitude, utterance trustworthy, so that teachers are required is trusted and imitated. One of the policies developed by the government of Indonesia to improve the quality of education is teacher certification. Teacher certification can be interpreted as a process of recognition that a person has to have the competence to carry out the educational services to certain educational unit, having passed the competency test held by the certification body.